Komunikasi Guru Pada Siswa Melalui Blended Learning Pada Penerapan PTMT di SMAN 5 Kota Sukabumi - Simamora, Santa Lorita; Suprianto, Toto; Saragih, Nurhayani (Brand Communication, 2023)
The purpose of this study is to understand and describe the communication between teachers and students through Blended Learning in the implementation of PTMT at SMAN 5 Kota Sukabumi. To describe this communication, various theories are utilized, including Berlo's theory, Gestalt theory, and the concept of group communication. This study is a qualitative research conducted as a case study. Data collection is done through interviews and observations. The research subjects are teachers and students, and the observations take place at SMAN 5 Kota Sukabumi, which implements the PTMT attendance pattern on odd and even days. The researcher observes blended learning sessions conducted by several teachers during both face-to-face and online sessions, including synchronous and asynchronous PJJ methods. After observing inside the classroom during the blended learning process, the researcher conducts interviews. Then, based on the observation and interviews, the researcher describes the communication between teachers and students using the aforementioned theories. The results of this study describe and depict the communication between teachers and students through Blended Learning in the implementation of PTMT at SMAN 5 Kota Sukabumi.